2011
DOI: 10.1016/j.chemgeo.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Selenium mobilization in soils due to volcanic derived acid rain: An example from Mt Etna volcano, Sicily

Abstract: The significant amounts of selenium (Se) emitted by volcanoes may have important impact on human health due to the narrow range between nutrition requirement and toxic effects for living organisms upon Se exposure. Although soils play a key role in determining the level in food and water and thereby human health, little is known about the behaviour of Se in volcanic soils. In this work we evaluated the Se release during rainwater-soil interaction under controlled conditions using soils collected on the flanks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…However, the mobility of Se may increase in volcanic soils after acid rainfall which may occur due to the interaction between volcanic gases and water vapor in atmosphere [38]. A past study showed that acid rain mobilized Se within volcanic soils which could lead to leaching of Se to aquifers [39]. The presence of other anions such as sulfate in acid rain can increase mobility of Se due to competition for adsorption on exchange sites in the soil since both S and Se are chemical analogs of each other and both are members of group VI on the periodic table with similar chemical properties [40].…”
Section: Volcanic Activitymentioning
confidence: 99%
“…However, the mobility of Se may increase in volcanic soils after acid rainfall which may occur due to the interaction between volcanic gases and water vapor in atmosphere [38]. A past study showed that acid rain mobilized Se within volcanic soils which could lead to leaching of Se to aquifers [39]. The presence of other anions such as sulfate in acid rain can increase mobility of Se due to competition for adsorption on exchange sites in the soil since both S and Se are chemical analogs of each other and both are members of group VI on the periodic table with similar chemical properties [40].…”
Section: Volcanic Activitymentioning
confidence: 99%
“…Volcanogenic Se is mobile due to its relatively low vaporization temperature. Oxidation and cooling processes in the atmosphere will transform Se to soluble selenite (SeO3 2− ) and selenate (SeO4 2− ) (Wen and Carignan, 2007) resulting in its high concentrations in the plume and therefore in snowfall and rainfall (Floor et al, 2011). Low amounts of Se have been found in Icelandic hay and herbage (Eiríksdóttir et al 1981, Símonarson et al 1984 resulting in Se deficiency occurring ubiquitously in lambs (Jóhannesson et al, 2007).…”
Section: Enrichment Ratios Of the Volatiles And Trace Metals In The Vmentioning
confidence: 99%
“…Volcanic hazards include degassing, volcanic gas dispersion, acid rain, pollution of surface waters, potential volcanic ash production and glacial outburst floods. These hazards have been previously investigated and used for civil-and environmental protection development in vicinities of the active volcanoes (e.g., Aiuppa, 2009;Aiuppa et al, 2006, Bagnato et al, 2013Björnsson, 2003;Bobrowski et al, 2007;Calabrese et al, 2011;Cuoco et al, 2013;D'Alessandro et al, 2013;Delmelle, 2003;Delmelle et al, 2002;Delmelle et al, 2007;Delmelle et al, 2015;Flaathen and Gislason, 2007;Floor et al,-2011;Galeczka et al, 2014;Gislason et al, 2002;2011;Gudmundsson et al, 1997Gudmundsson et al, , 2008Jones et al, 2011;Kristmannsdóttir et al, 1999;Moune et al, 2006;Menard et al, 2014;Oppenheimer 2003;Roberts et al, 2000;Russell et al, 2006Russell et al, , 2010Snorrason et al, 2002;Stefánsdóttir and Gislason, 2005;Thordarson and Self, 2003;Thordarson and Larsen, 2007;Tómasson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of current conditions indicate the potential role of acidic rainwater in the mobilization of metals (Floor et al, 2011). In this study, we assumed a pH between 3.3 and 4.3, which is typical of rainwater resulting from the mixing between volcanic plumes and atmospheric aerosols (Chudaeva et al, 2006;Calabrese et al, 2011;Floor et al, 2011). These values were measured in the neighborhood of active volcanoes such as Mount Etna.…”
mentioning
confidence: 99%